Gestión de las cuentas por cobrar franquicias y su incidencia en la liquidez de la empresa farmacias keyla s.a de la ciudad de guayaquil, en el periodo del 2022. - Vaicilla Gallo, Nadia Vanessa (2023)
The purpose of this research work is to determine how the management of accounts receivable franchises affects the liquidity of the company Farmacias Keyla S.A. of the city of Guayaquil, in the period 2022, this company since it began to offer franchises to third parties began to present problems in the account: accounts receivable franchises, because it did not have a management of accounts receivable in franchises fact that has generated that this account does not have an adequate return thus generating that the company Farmacias Keyla develops problems in its liquidity.This study is part of the mixed research method approach, because the type of research used is according to its purpose applies and according to its descriptive level of study, in this way the research will be based on research instruments to provide accurate and clear results on the problem that revolves around the company Keyla Pharmacies